2015
DOI: 10.1615/critreveukaryotgeneexpr.2015014042
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Mesenchymal Transition and Vascular Mimicry in Breast Cancer Stem Cells

Abstract: Vasculogenic mimicry (VM), a newly defined pattern of tumor microvascularization differs from angiogenesis and vasculogenesis in its noninvolvement of endothelial cells, by which highly aggressive tumor cells can form vessel-like structures themselves, because of their high plasticity. The presence of VM has been shown to be strongly associated with a poor prognosis in several types of cancer, but biological features of tumor cells that form VM remains unknown. Human breast cancer, characterized by a group of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 0 publications
4
26
0
Order By: Relevance
“…p38γ MAPK-enhanced EMT is accompanied by an increase in cancer stem cells (CSCs), which was consistent with the findings showing that induction of EMT is associated with the presence of cancer stem cells (CSCs) [13, 32]. We further delineated a down-stream signaling pathway that may mediate the action of p38γ MAPK (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…p38γ MAPK-enhanced EMT is accompanied by an increase in cancer stem cells (CSCs), which was consistent with the findings showing that induction of EMT is associated with the presence of cancer stem cells (CSCs) [13, 32]. We further delineated a down-stream signaling pathway that may mediate the action of p38γ MAPK (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…EMT also plays a crucial role for cancer progression, and contributes to the dissemination of cancer cells from solid tumors and the formation of detectable metastases [11]. EMT has also been implicated in therapy resistance, relapse, immune escape, and maintenance of cancer stem cell properties, such as self-renewal capacity [12, 13]. Understanding the complex events that lead to the EMT will therefore help to design new therapies against metastatic breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, VM is a known novel vascular network pattern that is formed by tumour cells but not endothelial cells in various cancers, including breast cancer, glioma and PCa . The VM structure was firstly reported by Maniotis et al, and the VM is formed by aggressive tumour cells gaining the characteristics of transdifferentiation and acquiring endothelial cell behaviour to access nutrition and initiate metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial-mesenchymal transition-like phenotype can be induced by hypoxic microenvironment which is of great significance in inducing VM in cancer cells. This phenotype is characterized with increased motility and invasiveness, and fibroblast-like cell-cell adhesion, which allows the cells to break free from the primary tumour site and metastasize at distant sites [26,27]. Moreover, it is demonstrated that EMT-related transcription factors are up-regulated in VM-forming tumour cells.…”
Section: Background Of Emtmentioning
confidence: 99%